Actress : a novel - Enright, Anne, 1962- (W. W. Norton & Company, 2020)
"From the Man Booker Prize-winner, a brilliant and moving novel about celebrity, sexual power, and a daughter's search to understand her mother's hidden truths. Katherine O'Dell is an Irish theater legend. As her daughter Norah retraces her mother's celebrated career and bohemian life, she delves into long-kept secrets, both her mother's and her own. Katherine began her career on Ireland's bus-and-truck circuit before making it to London's West End, Broadway, and finally Hollywood. Every moment of her life is a star turn, with young Norah standing in the wings. But the mother-daughter romance cannot survive Katherine's past or the world's damage. With age, alcohol, and dimming stardom, her grip on reality grows fitful and, fueled by a proud and long-simmering rage, she commits a bizarre crime. Her mother's protector, Norah understands the destructive love that binds an actress to her audience, but also the strength that an actress takes from her art. Once the victim of a haunting crime herself, Norah eventually becomes a writer, wife, and mother, finding her way to her own hard-won joy. Actress is finally a book about the freedom we find in our work and in the love we make and keep."--